Preparation, characterization and biodegradability performance of poly(3-hydroxybutyric acid)/polyvinyl acetate films / Olla H. S. Sharhan - H. S. Sharhan, Olla (2015)

(untitled)
In this work, microbial polyester, poly(3-hydroxybutyric acid) (PHB) was blended with polyvinyl acetate (PVAc) in various composition %(100/0, 95/5, 90/10, 85/15, 80/20, 75/25, 70/30, 65/35 and 0/100) and the film for each ratio was prepared by the solution casting method. The prepared films were then characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) for information regarding chemical structure and surface morphology of the films. Thermal stability of the blends was investigated by thermogravimetric analysis (TGA) while the melting point and glass transition temperatures (Tg) were investigated by Differential Scanning Calorimetry (DSC) at a heating rate of 10 oC min-1. Results showed that the thermal stability increased with increasing PVAc ratio. In addition the blends were also characterized by X-Ray Diffraction (XRD). For the biodegradability studies the films were buried in the soil for various specified days followed by chemical analysis. Intermolecular hydrogen bonding was observed from FTIR spectra and the best improvement in thermal stability and mechanical properties was shown by the blend ratio of PHB/PVAc (65/35). Biodegradability of the blends was studied by volume change measurement at room temperature and it was found to improve with increasing PVAc content. Blends of poly(hydroxyalkanoate) (PHA) with other biodegradable polymers also usually show similar improved biodegradability when compared with pure poly (hydroxyalkanoates) (PHAs).